WIDENING ACCESS IS THE END OF STORY? ENSURING EQUAL ACCESS AND IMPROVING CONTINUATION RATIO OF HIGHER EDUCATION IN INDONESIA - Rizqy Amelia Zein (Research Centre for Population, Indonesian Institute of Sciences, 2016)
In the last two decades, Indonesian higher education system has expanded rapidly in regards to the number of new established institutions and the number of students enrolled in higher education. However, the participation rate within university level is stated as low. In 2016, it only reached 31 percent. It means, although massification has been implemented within higher education system, it is not in line in ensuring equal access to pupils from disadvantaged social groups such as women, lower socio-economic statuses, and students from outer or periphery areas. Rather, it has been evident as a daunting task. Widening participation is not the end of story, since Indonesia should be dealing with another problem which is non-continuation. By performing secondary analysis on several datasets released by World Bank, Indonesian Ministry of Research, Technology and Higher Education, and Indonesian Statistics Bureau, this paper explores several major findings on accessibility and retention problem of Indonesian higher education.